Peak Current Control in Discontinuous Conduction Mode of Boost PFC - YAN Kaige; LIU Kun; PAN Yingying; GAN Yiyang (Kongzhi Yu Xinxi Jishu)
Peak current control is widely used in Boost power factor correction( PFC) converter, but mainly used in continuous conduction mode (CCM). Since the sinusoidal peak fitting curve is used in the discontinuous conduction mode (DCM), the average curve of a current cannot be sinusoidal and the power factor (PF) is low. In this paper, based on the calculated current characteristics in the DCM mode, a peak fitting curve was derived, and it can be used to improve the power factor. Moreover, to a certain extent, it constitutes a closed-loop control of the inductor current, which improves the reliability of the circuit. By PSIM software simulation and prototype experiment, the control method was proved to be effective.